Vomiting-Induced Gastric Emphysema and Hepatoportal Venous Gas: A Case Report and Review of the Literature. (11th February 2015) - Parikh, Malav P.; Sherid, Muhammed; Ganipisetti, Venu; Gopalakrishnan, Venu; Habib, Maria; Tripathi, Monika
Abstract : Gastric pneumatosis is the presence of air within the wall of the stomach. It represents a spectrum of conditions ranging from benign disease to septic shock and death. Etiopathologically, it can be classified into emphysematous gastritis or gastric emphysema (GE). Along with hepatoportal venous gas (HPVG), it was considered as an ominous radiological sign and warranted an emergent surgical exploration; however, with widespread use of computerized tomographic (CT) scan, an increasing number of benign causes of GE and HPVG have been reported in the literature, where patients can be managed by noninvasive and conservative measures. We hereby describe a case where recurrent episodes of vomiting led to development of GE and HPVG and the patient was managed successfully by conservative measures.